P269 A new dedicated capsule for diagnosis and monitoring of Crohn's disease. First patient series. (16th January 2018) - Calabrese, C; Calafiore, A; Gionchetti, P; Tontini, G E; Rizzello, F; Vecchi, M; Campieri, M
Abstract: Background: Crohn's disease (CD) is a chronic, disabling, life-long disease that can affect any portion of the gastrointestinal (GI) tract. Terminal ileum is the most frequent disease localisation, but several studies have shown a concomitant upper GI involvement in about 50% of patients. Proximal small bowel (SB) involvement is generally examined by cross sectional radiology techniques but in the last decade the capsule endoscopy (CE) has shown higher sensibility in detecting inflammatory lesions throughout the bowel and a very high negative predictive value in suspected CD. In confirmed CD the CE can be useful to evaluate disease extension and activity. The aim of this study is to evaluate the benefits of a new Crohn's PillCam Capsule (SBC) for the diagnosis and follow-up of CD, in the first 18 patients-series in Italy. Methods: Eighteen patients (12F; mean age 36.7 ± 15.3 years) underwent CE with SBC (8 suspected CD and 10 for known CD). For every patient, we assessed gastric and intestinal transit time and the presence of inflammatory lesions, evaluated by Lewis score (LS). Results: Table 1 summarises transit time data and observed lesions. Large bowel was assessed in all patients and no procedure-related complications were observed. No patient had capsule retention. In patients with suspected CD, major inflammatory lesions (ulcers/stenosis) were found in 50% overall, more frequently in the third tertile (75%). No major lesion was found in the first tertile, while minimal lesions (oedema/hyperaemia) was found in every patient with suspected CD. In patients with known CD we found major lesions in 9 out of 10 patients. These are more frequently located in the terminal or neoterminal ileum, while minimal lesions are more common in the first tertile. In CD patients, mean Lewis Score was 375 (465). In patients with suspected CD the mean LS was 143 (177). In patients with suspected CD, the CE examination took us to confirm the diagnosis in 75% of cases. Conclusions: CE has revolutionised the diagnosis and monitoring of SB CD. The procedure is patient-friendly and non-invasive with highest sensitivity in the evaluation of mucosal damage. The recognition that the severity of mucosa damage and its modification over time has strict implication with prognosis and management, should prompt the clinicians to a more extensive integration of CE in this field.